Acculturation and Diabetes Among Hispanics: Evidence from the 1999–2002 National Health and Nutrition Examination Survey - Mainous, Arch G (Association of Schools of Public Health, 2006)
OBJECTIVE: Hispanic individuals in the United States have a greater prevalence of diabetes mellitus than non-Hispanic white individuals; however, it is unclear whether Hispanics' risk of diabetes differs based on their level of acculturation. The purpose of our research was to examine acculturation among Hispanic Americans with respect to prevalence and control of diabetes. METHODS: We conducted an analysis of the National Health and Nutrition Examination Survey (NHANES), 1999–2002, a nationally representative sample of the noninstitutionalized U.S. population. We evaluated data on Hispanic adults (≥18 years of age, unweighted n=2,696), analyzing diagnosed diabetes, glycemic blood pressure and lipid control, and diabetes complications according to acculturation as measured by language and birth outside the United States. RESULTS: Hispanics with low acculturation were more likely to be without a routine place for health care, have no health insurance, and have low levels of education. In adjusted analyses, individuals with low acculturation, measured by language, were more likely to have diabetes (odds ratio [OR] 1.90, 95% confidence interval [CI] 1.02, 3.54). Among individuals with diagnosed diabetes, no significant association was yielded between acculturation and diabetes control. However, individuals with low language acculturation were more likely to have the diabetes complication of peripheral neuropathy (OR 4.01, 95% CI 1.40, 11.48). CONCLUSIONS: Acculturation as measured through language is associated with diabetes and complications among Hispanics even after controlling for a variety of demographic characteristics including health insurance and education. The findings suggest that even within a “single” minority ethnic group, there are differences in disease prevalence and complications and access to health care.